RFID and smart spaces. (10th December 2007) - Riekki, Jukka
RFID technology can be used in smart spaces to implement physical user interfaces. These user interfaces communicate the context-aware and pervasive services, which are available in the local environment to the user and allow the services to be activated easily. We present a general framework for activating services by touching RFID tags. The focus is on RFID icons, the visual representation on RFID tags, but we also discuss the middleware and the data stored on tags. We present several prototypes and the first usability tests as well.